Assessment of awareness level about consequences of missing teeth in Qassim region, Saudi Arabia - Rayan Saleh Al-Mutairi; Bayan Almohaimeed (PLoS ONE, 2025)
Missing teeth is a prevalent dental health problem that can lead to several unfavorable consequences, including dental caries, periodontal disease, bone deterioration, jaw disorders, malocclusion, and irregular teeth alignment. This Study aims to assess awareness of the consequences of missing teeth in the Qassim region, Saudi Arabia. A cross-section study was conducted, including 216 Saudi adults from Qassim, while children were excluded. Data were collected using an online questionnaire, which consisted of two parts: the first part gathered participants’ demographic data, and the second part included questions assessing their awareness level regarding teeth loss. Descriptive statistical analysis, bivariate chi-square test, and multivariate logistic regression analysis were performed using SAS OnDemand for academics. Among the 216 participants, 129 (59.7%) were females and 69 (31.9%) were between the ages of 26 and 35. The study revealed that 60.2% of participants were knowledgeable about treatment options for missing teeth. However, a lack of knowledge regarding available treatment options was significantly associated with age (P-value < .0001), education level (P-value 0.0336), and income level (P-value 0.0037). In this study, only 62.5% of participants reported being aware of the consequences of missing teeth. A significant number of the participants lacked awareness of these consequences, with the highest percentage of unawareness observed among the uneducated. Hence, educating patients about the complications of not replacing missing teeth is crucial, as it can improve their attitude toward treatment and enhance their quality of life.